Maternal diabetes alters the development of ductus venosus shunting in the fetus. (20th June 2018) - Lund, Agnethe; Ebbing, Cathrine; Rasmussen, Svein; Kiserud, Torvid; Kessler, Jörg
Abstract: Introduction: Despite adequate glycemic control, the risks of fetal macrosomia and perinatal complications are increased in diabetic pregnancies. Adjustments of the umbilical venous distribution, including increased ductus venosus shunting, can be important fetal compensatory mechanisms, but the impact of pregestational diabetes on umbilical venous and ductus venosus flow is not known. Material and methods: In this prospective study, 49 women with pregestational diabetes mellitus underwent monthly ultrasound examinations from gestational week 20 to 36. The blood velocity and the mean diameters of the umbilical vein and ductus venosus were used for calculating blood flow volumes. The development of the umbilical venous flow, ductus venosus flow and ductus venosus shunt fraction (% of umbilical venous blood shunted through the ductus venosus) was compared with a reference population, and the effect of HbA1c on the ductus venosus flow was assessed. Results: The umbilical venous flow was larger in pregnancies with pregestational diabetes mellitus than in low‐risk pregnancies ( p < 0.001) but smaller when normalized for fetal weight ( p = 0.036). The distributional pattern of the ductus venosus flow developed differently in diabetic pregnancies, particularly during the third trimester, being smaller ( p = 0.007), also when normalized for fetal weight ( p < 0.001). Correspondingly, the ductus venosus shunt fraction was reduced ( p < 0.0001), most prominently at 36 weeks. There were negative relations between the maternal HbA1c and the ductus venosus flow velocity, flow volume and shunt fraction. Conclusions: In pregnancies with pregestational diabetes mellitus, prioritized umbilical venous distribution to the fetal liver and lower ductus venosus shunt capacity reduce the compensatory capability of the fetus and may represent an augmented risk during hypoxic challenges during late pregnancy and birth.